M. Robert Guggenheim trophy, Alaska Yukon Pacific Exposition, Seattle, 1909 - Nowell, Frank H., 1864-1950 (1909)
This trophy was awarded to the winner of the trans-continental race from New York to Seattle. PH Coll 727.768 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number